2010
DOI: 10.1002/glia.20983
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid and cannabinoid‐like receptors in microglia, astrocytes, and astrocytomas

Abstract: CB1 and CB2 receptors are activated by a plethora of cannabinoid compounds, be they endogenously-produced, plant-derived or synthetic. These receptors are expressed by microglia, astrocytes and astrocytomas, and their activation regulates these cells' differentiation, functions and viability. Recent studies show that glial cells also express cannabinoid-like receptors, and that their activation regulates different cell functions, but also control cell viability. This review summarizes this evidence, and discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
363
2
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 455 publications
(382 citation statements)
references
References 153 publications
11
363
2
6
Order By: Relevance
“…We observed only weak CB 2 immunostaining in GFAP-labeled astrocytes and no CB 2 immunostaining in CD11b-labeled microglia. These findings are consistent with previous reports that microglia and astrocytes may not express CB 2 Rs in healthy rats and mice (14,(41)(42)(43). More studies are required to address it.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We observed only weak CB 2 immunostaining in GFAP-labeled astrocytes and no CB 2 immunostaining in CD11b-labeled microglia. These findings are consistent with previous reports that microglia and astrocytes may not express CB 2 Rs in healthy rats and mice (14,(41)(42)(43). More studies are required to address it.…”
Section: Discussionsupporting
confidence: 92%
“…It has been reported that CB 2 Rs are expressed and up-regulated in microglia during neuroinflammation in humans (21,41). Our experiments did not reveal obvious CB 2 R immunostaining in glial cells in the VTA.…”
Section: Discussioncontrasting
confidence: 65%
“…Both astrocytes and microglia express CB1 and CB2 cannabinoid receptors in an activity-dependent manner [183][184][185]. In the microglia, the expression of CB2 receptor exceeds the expression of CB1 receptors and correlates with microglial phenotype and activity [186]. Activation of glial CB2 receptors attenuates glial activation [187] and prevents neurodegeneration and reduces symptoms in mouse model of Huntington's disease [188].…”
Section: (D) Regulation Of Glial Activitymentioning
confidence: 99%
“…Astrocytes and microglial cells can synthesize endocannabinoids because they express enzymes involved in the synthesis (12,13) and degradation (13,14) of endocannabinoids. In the central nervous system, cannabinoid type 1 (CB1) receptors are found primarily on neurons and at a marginal level, on glial cells (15). The expression of CB1 receptors varies between brain areas and neuronal cell types.…”
mentioning
confidence: 99%